Neonatal cerebral infarction and visual function at school age. Issue 6 (1st November 2003) - Mercuri, E; Anker, S; Guzzetta, A; Barnett, A; Haataja, L; Rutherford, M; Cowan, F; Dubowitz, L; Braddick, O; Atkinson, J
Abstract : Objective: To assess various aspects of visual function at school age in children with neonatal cerebral infarction. Patients and methods: Sixteen children born at term, who had cerebral infarction of perinatal onset on neonatal magnetic resonance imaging (MRI) were assessed using a battery of visual tests. This included measures of crowding acuity (Cambridge Crowding Cards), stereopsis (TNO test), and visual fields. The results of the visual assessment were compared with the type and the extent of the lesion observed on neonatal MRI. Results: Only six of the 16 children (28%) had some abnormalities of visual function on these tests. Visual abnormalities were more common in children with more extensive lesions involving the main branch of the middle cerebral artery and were less often associated with lesions in the territory of one of the cortical branches of the middle cerebral artery. The presence of visual abnormalities was not always associated with the involvement of optic radiations or occipital primary visual cortex. Abnormal visual fields were only found in children who also developed hemiplegia. Conclusions: Abnormality of visual function is not common in children who had neonatal infarction and, when present, tends to be associated with hemiplegia and more extensive lesions.